Error Functions, Dawson’s and Fresnel Integrals - 7.4 Symmetry

From testwiki
Revision as of 11:15, 28 June 2021 by Admin (talk | contribs) (Admin moved page Main Page to Verifying DLMF with Maple and Mathematica)
(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)
Jump to navigation Jump to search


DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
7.4.E1 erf ( - z ) = - erf ( z ) error-function 𝑧 error-function 𝑧 {\displaystyle{\displaystyle\operatorname{erf}\left(-z\right)=-\operatorname{% erf}\left(z\right)}}
\erf@{-z} = -\erf@{z}

erf(- z) = - erf(z)
Erf[- z] == - Erf[z]
Successful Successful - Successful [Tested: 7]
7.4.E2 erfc ( - z ) = 2 - erfc ( z ) complementary-error-function 𝑧 2 complementary-error-function 𝑧 {\displaystyle{\displaystyle\operatorname{erfc}\left(-z\right)=2-\operatorname% {erfc}\left(z\right)}}
\erfc@{-z} = 2-\erfc@{z}

erfc(- z) = 2 - erfc(z)
Erfc[- z] == 2 - Erfc[z]
Successful Successful - Successful [Tested: 7]
7.4.E4 F ( - z ) = - F ( z ) Dawsons-integral 𝑧 Dawsons-integral 𝑧 {\displaystyle{\displaystyle F\left(-z\right)=-F\left(z\right)}}
\DawsonsintF@{-z} = -\DawsonsintF@{z}

dawson(- z) = - dawson(z)
DawsonF[- z] == - DawsonF[z]
Successful Successful - Successful [Tested: 7]
7.4#Ex1 C ( - z ) = - C ( z ) Fresnel-cosine-integral 𝑧 Fresnel-cosine-integral 𝑧 {\displaystyle{\displaystyle C\left(-z\right)=-C\left(z\right)}}
\Fresnelcosint@{-z} = -\Fresnelcosint@{z}

FresnelC(- z) = - FresnelC(z)
FresnelC[- z] == - FresnelC[z]
Successful Successful - Successful [Tested: 7]
7.4#Ex2 S ( - z ) = - S ( z ) Fresnel-sine-integral 𝑧 Fresnel-sine-integral 𝑧 {\displaystyle{\displaystyle S\left(-z\right)=-S\left(z\right)}}
\Fresnelsinint@{-z} = -\Fresnelsinint@{z}

FresnelS(- z) = - FresnelS(z)
FresnelS[- z] == - FresnelS[z]
Successful Successful - Successful [Tested: 7]
7.4#Ex3 C ( i z ) = i C ( z ) Fresnel-cosine-integral 𝑖 𝑧 𝑖 Fresnel-cosine-integral 𝑧 {\displaystyle{\displaystyle C\left(iz\right)=iC\left(z\right)}}
\Fresnelcosint@{iz} = i\Fresnelcosint@{z}

FresnelC(I*z) = I*FresnelC(z)
FresnelC[I*z] == I*FresnelC[z]
Successful Successful - Successful [Tested: 7]
7.4#Ex4 S ( i z ) = - i S ( z ) Fresnel-sine-integral 𝑖 𝑧 𝑖 Fresnel-sine-integral 𝑧 {\displaystyle{\displaystyle S\left(iz\right)=-iS\left(z\right)}}
\Fresnelsinint@{iz} = -i\Fresnelsinint@{z}

FresnelS(I*z) = - I*FresnelS(z)
FresnelS[I*z] == - I*FresnelS[z]
Successful Successful - Successful [Tested: 7]
7.4#Ex5 f ( i z ) = ( 1 / 2 ) e 1 4 π i - 1 2 π i z 2 - i f ( z ) Fresnel-auxilliary-function-f 𝑖 𝑧 1 2 superscript 𝑒 1 4 𝜋 𝑖 1 2 𝜋 𝑖 superscript 𝑧 2 𝑖 Fresnel-auxilliary-function-f 𝑧 {\displaystyle{\displaystyle\mathrm{f}\left(iz\right)=(1/\sqrt{2})e^{\frac{1}{% 4}\pi i-\frac{1}{2}\pi iz^{2}}-i\mathrm{f}\left(z\right)}}
\auxFresnelf@{iz} = (1/\sqrt{2})e^{\frac{1}{4}\pi i-\frac{1}{2}\pi iz^{2}}-i\auxFresnelf@{z}

Fresnelf(I*z) = (1/(sqrt(2)))*exp((1)/(4)*Pi*I -(1)/(2)*Pi*I*(z)^(2))- I*Fresnelf(z)
FresnelF[I*z] == (1/(Sqrt[2]))*Exp[Divide[1,4]*Pi*I -Divide[1,2]*Pi*I*(z)^(2)]- I*FresnelF[z]
Failure Failure Successful [Tested: 7] Successful [Tested: 7]
7.4#Ex6 g ( i z ) = ( 1 / 2 ) e - 1 4 π i - 1 2 π i z 2 + i g ( z ) Fresnel-auxilliary-function-g 𝑖 𝑧 1 2 superscript 𝑒 1 4 𝜋 𝑖 1 2 𝜋 𝑖 superscript 𝑧 2 𝑖 Fresnel-auxilliary-function-g 𝑧 {\displaystyle{\displaystyle\mathrm{g}\left(iz\right)=(1/\sqrt{2})e^{-\frac{1}% {4}\pi i-\frac{1}{2}\pi iz^{2}}+i\mathrm{g}\left(z\right)}}
\auxFresnelg@{iz} = (1/\sqrt{2})e^{-\frac{1}{4}\pi i-\frac{1}{2}\pi iz^{2}}+i\auxFresnelg@{z}

Fresnelg(I*z) = (1/(sqrt(2)))*exp(-(1)/(4)*Pi*I -(1)/(2)*Pi*I*(z)^(2))+ I*Fresnelg(z)
FresnelG[I*z] == (1/(Sqrt[2]))*Exp[-Divide[1,4]*Pi*I -Divide[1,2]*Pi*I*(z)^(2)]+ I*FresnelG[z]
Failure Failure Successful [Tested: 7] Successful [Tested: 7]
7.4#Ex7 f ( - z ) = 2 cos ( 1 4 π + 1 2 π z 2 ) - f ( z ) Fresnel-auxilliary-function-f 𝑧 2 1 4 𝜋 1 2 𝜋 superscript 𝑧 2 Fresnel-auxilliary-function-f 𝑧 {\displaystyle{\displaystyle\mathrm{f}\left(-z\right)=\sqrt{2}\cos\left(\tfrac% {1}{4}\pi+\tfrac{1}{2}\pi z^{2}\right)-\mathrm{f}\left(z\right)}}
\auxFresnelf@{-z} = \sqrt{2}\cos@{\tfrac{1}{4}\pi+\tfrac{1}{2}\pi z^{2}}-\auxFresnelf@{z}

Fresnelf(- z) = sqrt(2)*cos((1)/(4)*Pi +(1)/(2)*Pi*(z)^(2))- Fresnelf(z)
FresnelF[- z] == Sqrt[2]*Cos[Divide[1,4]*Pi +Divide[1,2]*Pi*(z)^(2)]- FresnelF[z]
Successful Successful - Successful [Tested: 7]
7.4#Ex8 g ( - z ) = 2 sin ( 1 4 π + 1 2 π z 2 ) - g ( z ) Fresnel-auxilliary-function-g 𝑧 2 1 4 𝜋 1 2 𝜋 superscript 𝑧 2 Fresnel-auxilliary-function-g 𝑧 {\displaystyle{\displaystyle\mathrm{g}\left(-z\right)=\sqrt{2}\sin\left(\tfrac% {1}{4}\pi+\tfrac{1}{2}\pi z^{2}\right)-\mathrm{g}\left(z\right)}}
\auxFresnelg@{-z} = \sqrt{2}\sin@{\tfrac{1}{4}\pi+\tfrac{1}{2}\pi z^{2}}-\auxFresnelg@{z}

Fresnelg(- z) = sqrt(2)*sin((1)/(4)*Pi +(1)/(2)*Pi*(z)^(2))- Fresnelg(z)
FresnelG[- z] == Sqrt[2]*Sin[Divide[1,4]*Pi +Divide[1,2]*Pi*(z)^(2)]- FresnelG[z]
Successful Failure - Successful [Tested: 7]